Effects of High-Fat Diet on eHSP72 and Extra-to-Intracellular HSP70 Levels in Mice Submitted to Exercise under Exposure to Fine Particulate Matter - Kostrycki, I.; Wildner, G.; Donato, Y.; Dos Santos, A.; Beber, L.; Frizzo, M.; Ludwig, M.; Keane, Kevin; Cruzat, Vinicius; Rhoden, C.; Heck, T. (Hindawi Publishing Corporation, 2019)
Obesity, air pollution, and exercise induce alterations in the heat shock response (HSR), in both intracellular 70?kDa heat shock proteins (iHSP70) and the plasmatic extracellular form (eHSP72). Extra-to-intracellular HSP70 ratio (H-index?=?eHSP70/iHSP70 ratio) represents a candidate biomarker of subclinical health status. This study investigated the effects of moderate- and high-intensity exercise in the HSR and oxidative stress parameters, in obese mice exposed to fine particulate matter (PM2.5). Thirty-day-old male isogenic B6129F2/J mice were maintained for 16 weeks on standard chow or high-fat diet (HFD). Then, mice were exposed to either saline or 50?µg of PM2.5 by intranasal instillation and subsequently maintained at rest or subjected to moderate- or high-intensity swimming exercise. HFD mice exhibited high adiposity and glucose intolerance at week 16th. HFD mice submitted to moderate- or high-intensity exercise were not able to complete the exercise session and showed lower levels of eHSP70 and H-index, when compared to controls. PM2.5 exposure modified the glycaemic response to exercise and modified hematological responses in HFD mice. Our study suggests that obesity is a critical health condition for exercise prescription under PM2.5 exposure.